Analisis Prospektif Peremajaan Kelapa Sawit (Elaeis Guineensis Jacq) Pola Swadaya di Kabupaten Rokan Hulu - Andy Utomo Gurusinga; Novia Dewi; Rosnita Rosnita (Hasanuddin University, 2022)
This study aims to analyze self-help oil palm farming and determine the key attributes in the rejuvenation of self-help oil palm plantations and the implications of self-help oil palm rejuvenation in Rokan Hulu Regency. This research was conducted in three sub-districts in Rokan Hulu Regency, Riau Province. The three sub-districts are Rambah Samo, Rambah Hilir, and Hulu sub-districts. The sampling of a representative area is by using the Multistage Area Sampling consisting of 9 villages with a sample of 90 oil palm farmers. The results of this study indicate that self-help oil palm farming in Rokan Hulu has an RCR value of > 1, meaning that oil palm farming in Rokan Hulu is feasible. The RCR value of oil palm farming in Rokan Hulu is 1.57 and the determinant attributes for farmers' attitudes in supporting oil palm rejuvenation activities consist of banking activities, cooperative members and cultivation techniques. These attributes have a strong influence on farmers' attitudes as well as the implications of developing self-help oil palm rejuvenation in this study, namely improvements in the attributes of human resources, ease of selling results, capital and legality. This applies as a consideration for the farmers themselves.